Xi’s Visit to Russia : Beginning of a New Era? - Cheang, Chris (2019)
Bilateral relations between China and Russia have been strengthened with President Xi Jinping’s latest state visit to Moscow. However, growing links with China will not change Russia’s entrenched Eurocentric orientation.